Mobile communication WCDMA (3G) mobile network architecture - Verma, Brijesh (S.K. Kataria & Sons, 2012)
The rapid growth of mobile communication and its pervasive use are changing the way we communicate in some fundamental ways, modern communication distinguishes itself with the treament of these techniques in depth and yet in a principle manner that can be taught at the undergraduate level. The order in which these techniques are treated follows the evolution of spectral evolution of spectral utilizationin various mudulation techniques. As consequences, much of the material in the book is presented in the order in which it was actually developed, giving students insight into the logic and need for each development.